Sustainable Revitalisation As A Tool For Regenerating The Attractiveness Of An Inner-City Historic Commercial District: 'Han District' As A Case - Köprülü-Bağbancı, Özlem; Akıncıtürk, Nilüfer; Vural-Arslan, Tülin; DOSTOĞLU, NESLİHAN (Palgrave Macmillan Ltd, Brunel Rd Bldg, Houndmills, Basingstoke Rg21 6Xs, Hants, England, 2011)
Retail activity and retail spaces have changed drastically across Turkey since the opening of first shopping mall in 1988. The boom of personal mobility (that is, the car) and the convenience of shopping at out-of-town shopping areas have caused profound transformations of the physical, social and economic structures of the historic commercial districts of Turkish city centres. Although certain revitalisation projects are being planned to develop and promote commercial activity in these districts with the aim of revitalising physical structures and regenerating social and economic activity, many of them do not use holistic approaches that take into account the physical, social and economic sustainability of the district. The focus of this study is to introduce a conceptual model of a sustainable revitalisation project for an inner-city historic commercial district in the Turkish city of Bursa. The aim of this project is to develop an integrated approach to the economic and social revitalisation of the commercial district that achieves more than just physical regeneration. The design team believes that the insight gained in this project is applicable to other revitalisation projects in different areas and is also valuable for formulating policies and appropriate codes for future projects. URBAN DESIGN International (2011) 16, 188-201. doi:10.1057/udi.2011.1; published online 16 February 2011
Keywords: sustainable revitalisation; inner-city revitalisation; historic commercial district; Bursa; economic-development; urban quarters; downtown; sürdürülebilir canlandırma; şehir içi canlandırma; tarihi ticaret bölgesi; ekonomik gelişme